A single session of sprint interval training increases total daily energy expenditure - Sevits, Kyle, author; Melby, Chris, advisor; Bell, Christopher, advisor; Gentile, Christopher, committee member; Browning, Ray, committee member; Melanson, Ed, committee member (Colorado State University. Libraries, 2014)
Background: Sprint interval training (SIT) is known to elicit favorable physiological adaptations, including improved insulin sensitivity and glucose tolerance. Its utility for weight maintenance is unclear. Presumably any effects would be mediated by increased energy expenditure during both the exercise itself, and during recovery. Therefore, the objective of this study is to determine the effects of a single bout of SIT on 24-hour energy expenditure (EE). Methods: 24-hour EE was determined in 12 healthy men (age: 26 ± 2 years; body mass index: 23.6 ± 0.5 kg/m2; mean ± SE). After three days of controlled diet and maintenance of energy balance, subjects were studied in a whole-room indirect calorimeter for two consecutive days. One of these days (random order) began with a single bout of SIT (5 x 30 second "all-out" exertions on a cycle ergometer against a resistance equivalent to 7.5% body mass, separated by 4 minutes of loadless cycling). Subjects spent the other day in the calorimeter without exercising. Results: An acute bout of SIT increased 24-hour EE in all subjects by an average of 226 ± 15 kcal during an otherwise sedentary day (Control: 2189 ± 58 vs. SIT: 2415 ± 62 kcal/day; P < 0.001). There was also a non-significant (P = 0.054) decrease in fat balance on the exercise day (control = -9.7 ± 7.9 g/day vs. SIT = -20.6 ± 8.2 g/day). Conclusions: Our data provide support for SIT as a time-efficient exercise to increase total daily energy expenditure and may aid in the maintenance of health.
Keywords: energy expenditure; exercise; physical activity; SIT; sprint; time